Corporate Liquidity and Solvency in Europe during COVID-19 : The Role of Policies - Ebeke, Christian (IMF Working Papers; Working Paper ;, 2021)
The spread of COVID-19, containment measures, and general uncertainty led to a sharp reduction in activity in the first half of 2020. Europe was hit particularly hard-the economic contraction in 2020 is estimated to have been among the largest in the world-with potentially severe repercussions on its nonfinancial corporations. A wave of corporate bankruptcies would generate mass unemployment, and a loss of productive capacity and firm-specific human capital. With many SMEs in Europe relying primarily on the banking sector for external finance, stress in the corporate sector could easily translate into pressures in the banking system (Aiyar and others, forthcoming).